Reforma de la Ley Orgánica De Contratación Publica y la COOTAD ya que la expropiación de bienes inmuebles por parte del estado vulnera los derechos constitucionales de los propietarios - Robles Cojitambo, Ernesto Fidel (2016)
The declaration of public utility allows the authority to prevent the premises determined to be necessary for the public service can not be sold to third parties for their owners, and to ensure that these properties will be used for the intended purpose. The declaration of public utility is the first step to take before making the expropriation, in normal cases this is done by the Municipal Council, and in cases of works or special services they may perform ministerial councils. In this type of procedure is crucial that the expert conducting the expert assessment of the land declared public utility criteria to get save objectivity impartiality when determining the value of the objects of expropriation, to thereby minimize the level conflict that may exist with the owners. To this end the various public institutions shall be governed by the following laws: • Constitution of the Republic of Ecuador. • Code of Civil Procedure. • Organic Law of the National System of Public Procurement (LOSNCP). • General Regulations to the Organic Law of the National System of Public Procurement. While Municipalities have COOTAD into law , from Art Art 446-459 and 594-596 . For the expropriation of immovable property shall be taken into account two criteria, which are for public use or public utility and social interest. The public is expropriation and when public interest is to be performed in that place a work that benefits an entire community or cluster while to expropriate land for a social interest , for example, involve a housing program for group of people in need. While Expropriation has its own rules and procedure to be followed, in which I must framing, these provisions are worthy to explain and comment. The State, through the municipalities, provincial councils and other public institutions through its representatives or authorities may request the expropriation of property and declare public utility prior justification or community request. But the question would be the expropriation of some goods is justified to declare a public utility? Definitely yes, the State has every right to do whatever means possible expropriation, but always framed in law and respect for the owner of the property, which is not justified, and the state must observe and modify its wasteful policy inconsequential, insecurity and lack of guarantees to the owners. This study analyzes the changes in a serious way, its advantages and disadvantages made the laws. I am of the view that the state and sectional governments, municipalities, H. Provincial Councils and Institutions must expropriate the assets necessary for them to be used by the whole community, but only if paid to the plaintiff or the righteous affected areas, no harm and suffer losses of money and its heritage. Aspire that reading these few pages, envelop the reader interested in the expropriation and find in them the correct answer on the subject